A grounded theory study on family-to-work enrichment: Exploring links with family resources, community resources, work-role salience and psychological capital. Issue 1 (2nd March 2015) - Mishra, Pavitra
Abstract : Purpose: – The purpose of this paper is to demonstrate systematic application of grounded theory to understand antecedents, moderators and consequences of family-to-work enrichment in India. The paper throws light on the key tenets of grounded theory research and explains its use as a rigorous method for management research. Design/methodology/approach: – "Paradigm model" of grounded theory was used for data analysis. Data were collected through in-depth interviews of 24, middle managers in India. Interviewees were from various industries like IT, software, insurance, banking, telecom, media, consulting and fast moving consumer goods. Findings: – This study identifies family resources as an antecedent of family-to-work enrichment. Community resources and work-role salience facilitate positive relation between family resources and family-to-work enrichment. Further, psychological capital has been identified as a consequence. Strategies adopted by the professionals to enhance their family-to-work enrichment have also been explored. Research limitations/implications: – This study provides a holistic understanding of family-to-work enrichment, an under researched phenomenon by exploring relation between work, family and community resources. Practical implications: – The integration of three domains, i.e. work, family and community provide insights to managers and policy makers about the importance of family and community in the organizations. Originality/value: – This study fulfills the need to explore positive side of work-family interface especially, in emerging economies like India. Moreover, it is the first attempt to study the work-family-community interface from a grounded theory approach in the Indian context and probably one of the first few in the literature.